Comparison of protein extraction methods using Edible Bird's Nest (EBN) samples for protein identification - Muhammad Azzahar Ahmad (2018)
Rich in its nutritional elements, edible bird’s nest (EBN) has become one of the most expensive natural products EBN and comprised of two major constituents namely carbohydrate (46.7%) and protein (35.8%) with unusual abundance of glycoprotein. With proteomic analysis, identification of low abundance protein will uncover the secret of EBN. Prior to proteomic analysis, different methods of protein extraction were performed on farmed (fEBN) and commercialised EBN (cEBN) using aqueous extraction at 70˚C and 100˚C (with or without acetone precipitation method) as well as sodium dodecyl sulfate and Triton X-100 before protein quantification. Both samples showed that aqueous extraction at 100˚C with acetone precipitation extracted the highest protein concentration (fEBN = 8.744 ‡ 0.824; cEBN = 6.994 ‡ 1.059) due to high amount of water-soluble protein with an aid of acetone precipitation that contributed to protein precipitations formation. Triton X-100 extracted the least (fEBN = .0322 ‡ 0.032; cEBN = 0.053 ‡ 0.092) for both types of EBN samples due to its affinity to only poor water-soluble proteins. In conclusion, there were significance differences in protein yield different protein extraction methods for both EBN sample sources; but no significance difference between different sources of EBN samples for each method.
Also available in CD-ROM format.
Project paper (D.V.M) - Universiti Putra Malaysia, 2018.